PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI (STUDY KASUS DIPUSKESMAS KEMBAYAN KABUPATEN SANGGAU KALIMANTAN BARAT) - B2042191010, Nurul Huda (Universitas Tanjungpura, 2021)
PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI (STUDI KASUS DIPUSKESMAS KEMBAYAN KECAMATAN KEMBAYAN KABUPATEN SANGGAU KAPUAS) NURUL HUDAProgram Studi Magister Manajemen Fakultas EkonomiUniversitas Tanjungpura ABSTRACTThis study aims to determine and analyze (1) the influence of leadership style, organizational culture on work motivation and its impact on employee performance, (2) Knowing and testing the influence of leadership style, organizational culture and work motivation either partially or simultaneously on employee performance at the Puskesmas Kembayan. The population in this study were all employees of Kembayan Public Health Center, with the sampling technique of the entire population with a sample size of 77 people. This type of research is included in the explanatory research. Methods of data collection by distributing questionnaires and in-depth interviews. Methods of data analysis using Path Analysis with SPSS 22 software. The instrument used for data collection was a Likert scale model questionnaire.Based on the research results, the variables of leadership style, organizational culture, work motivation and employee performance at the Kembayan Health Center generally showed good results. From the results of the path analysis test, it can be concluded that: (1) the variable leadership style and organizational culture do not have a significant effect on work motivation. (2) Leadership style, work culture and work motivation have a significant effect on performance. Keywords: Leadership Style, Organizational Culture, Work Motivation and Employee Performance